PERBEDAAN TINGKAT DEMENSIA ANTARA SEBELUM DAN SESUDAH PELAKSANAAN SENAM OTAK PADA LANSIA DI PSTW BONDOWOSO - Zahruddin; Harianah Akib (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2016)
Dementia is a clinical syndrome which includes loss of intellectual function and memory that is so severe that it causes dysfunction in daily life. On March 9, 2014 researchers conducted a preliminary study at Bondowoso Social Assistance Center (PSTW). There are 140 elderly who are registered as PSTW residents. From interviews with the institution, 42% of the 140 residents had dementia. . The purpose of this study was to determine differences in the level of dementia between before and after the implementation of brain exercise in the elderly in Bondowoso PSTW 2014. The research design used was a comparison using a one-group interpretation-posttest design approach. Primary data were collected using questionnaire sheets and secondary data by looking at the recapitulation of Bondowoso PSTW data, then analyzed using the Wilcoxon test. The results of the study found that from sig. (2-tailed) of 0.001 shows that the p value is less than 0.005 so this shows that there are differences in the level of dementia between before and after the exercise of brain exercise in the elderly in Bondowoso in 2014. It is recommended that padalansia in Bondowoso PSTW always routinely perform brain exercise activities regularly as taught